2017
DOI: 10.1371/journal.pone.0182143
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Gcn2 in response to different stresses

Abstract: All organisms have evolved pathways to respond to different forms of cellular stress. The Gcn2 kinase is best known as a regulator of translation initiation in response to starvation for amino acids. Work in budding yeast has showed that the molecular mechanism of GCN2 activation involves the binding of uncharged tRNAs, which results in a conformational change and GCN2 activation. This pathway requires GCN1, which ensures delivery of the uncharged tRNA onto GCN2. However, Gcn2 is activated by a number of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 46 publications
1
74
0
Order By: Relevance
“…Under optimal growth conditions, eIF2 properly initiates translation. However, upon amino acid starvation or exposure to different stress conditions, the Gcn2 kinase is activated and phosphorylates eIF2α, which interferes with 5′cap-dependent mRNA translation 19,[28][29][30] . Consistent with this, we observed that the expression of the GCN4-lacZ reporter construct was not up-regulated by amino acid starvation (3-AT treatment) or upon iron depletion in a gcn2Δ mutant ( Fig.…”
Section: The Translational State Of Specific Transcripts Is Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…Under optimal growth conditions, eIF2 properly initiates translation. However, upon amino acid starvation or exposure to different stress conditions, the Gcn2 kinase is activated and phosphorylates eIF2α, which interferes with 5′cap-dependent mRNA translation 19,[28][29][30] . Consistent with this, we observed that the expression of the GCN4-lacZ reporter construct was not up-regulated by amino acid starvation (3-AT treatment) or upon iron depletion in a gcn2Δ mutant ( Fig.…”
Section: The Translational State Of Specific Transcripts Is Differentmentioning
confidence: 99%
“…under amino acid starvation conditions occurs through the binding of uncharged tRNAs to its histidyl-tRNA synthetase (HisRS)-like domain, a process that requires the Gcn1-Gcn20 protein complex 25,30 . To investigate whether the activation of Gcn2 kinase in response to iron deficiency was mediated by this mechanism, we analyzed the polysome profile of wild-type and gcn1∆ cells under iron-deficient conditions.…”
Section: The Repression Of Translation Under Iron Deficiency Dependsmentioning
confidence: 99%
“…Given the speed at which GCN2 is activated, the most likely candidates are a direct biochemical activation of the kinase by a redox-active compound or by an intermediate that is released from the chloroplast during ROS stress. This very question also remains unresolved in every other organism, fission yeast, budding yeast, mammals, where ROS-activation of eIF2a kinases has been observed over the past 15 years (Shenton et al, 2006;Anda et al, 2017) and remains to be explored in more detail.…”
Section: Gcn2 Activation By Light and Rosmentioning
confidence: 99%
“…In S. cerevisiae, divergent stresses other than AAS such as glucose deprivation and high salt activates Gcn4 in Gcn2-tRNA binding motif dependent manner indicating the accumulation of uncharged tRNA as the responsible mechanism [1]. Also in Schizosaccharomyces pombe (S. Pombe), uncharged tRNA binding to Gcn2 is essential for the response to AAS as well as to hydrogen peroxide (H 2 O 2 ) and UV radiation, and these responses require Gcn1 [9]. Recent analysis also showed that GCN2 mediates ISR activation by the unfolded protein response in PLOS GENETICS mitochondria (UPR mt ) in Caenorhabditis elegans (C. elegans) [10] and that its activation leads to longevity expansion in both C. elegans and Drosophila [10,11].…”
Section: Introductionmentioning
confidence: 99%